Morel-Lavallée syndrome and post-traumatic nodular fat necrosis: Two post-traumatic complications mimicking cellulitis - Moulin, C; Barthélémy, I; Emering, C; D'Incan, M (Annales de dermatologie et de vénéréologie, 2017)
Dermal and subcutaneous inflammation following direct trauma is initially evocative of soft-tissue infection. However, two differential diagnoses must be considered: Morel-Lavallée syndrome and post-traumatic nodular fat necrosis. Case 1: a 51-year-old woman fell off her motorbike and had dermabrasions on her right and left tibial ridges that rapidly developed into dermo-hypodermitis of the entire limb. There was no improvement after 3 weeks of antibiotics. The patient was apyretic. She had a soft, non-inflammatory tumefaction on the inner aspect of her left knee. Ultrasound revealed subcutaneous collection in both legs. The surgeons confirmed a diagnosis of Morel-Lavallée syndrome and drained the two collections. Progress was good and the patient healed without major consequences. Case 2: following a fall on her stairs, a 40-year-old woman presented dermabrasions and haematomas on her left leg. Antibiotic therapy failed to prevent the progression of dermo-hypodermitis. The patient remained apyretic and there was no inflammatory syndrome. A CT scan showed thickening of a subcutaneous fat and fluid collection, resulting in diagnosis of post-traumatic nodular fat necrosis. Management was surgical and the outcome was good. These two cases show two post-traumatic cutaneous complications: Morel-Lavallée syndrome and post-traumatic nodular fat necrosis. Morel-Lavallée syndrome occurs after tangential trauma next to richly vascularized tissue. Post-traumatic nodular fat necrosis is defined as necrosis of adipocytes. In both cases, diagnosis is confirmed by imagery (Ultrasonography, tomography). Our two case reports show that inflammatory presentation of both Morel-Lavallée syndrome and post-traumatic nodular fat necrosis can lead to diagnostic and therapeutic errors while a surgical procedure is necessary since tissue necrosis can occur.